Marketing Politik Pasangan Hendrar Prihadi – Hevarita Gunaryanti Rahayu Dalam Pilkada Tahun 2015 Di Kota Semarang - Larasanti, Firna; Susanti, Martien Herna; Suhardiyanto, Andi (Universitas Negeri Semarang, 2017)
Political marketing are all means used in political campaigns to influence voters' choices. The purpose of this study was to determine: 1) Political marketing applying pair Hendi - Ita in the elections of 2015 in the city of Semarang. 2) Supporting and inhibiting factors. Test the validity of the data using triangulation. Data analysis was performed through four grooves namely the collection, reduction, presentation and verification of data. The results showed that 1) Pair-ita Hendi can apply with good political marketing. This is evidenced in which the couple did not take a long time and is difficult to embed the political image as the figure that has been known by the public. The images-images that are sold in the nomination, campaign and political promises. 2) The supporting factors that figure and track record, the incumbent, the bearer party support for the winning team and a team of volunteers, to build a network-based organization and network with community leaders. Whereas the inhibiting factor that is limiting the open campaign. The proposed recommendation is 1) The election of pair-Ita Hendi as Mayor and Deputy Mayor of Semarang from 2015 to 2020 they had to run what has been promised. 2) Need to political education for the community that pilihanya according to the thinking and logical consideration.